On the diagnosis of intrauterine listeriosis - A. A. Nafeev; V. I. Modnikova; V. V. Popov; N. P. Gorbikova; F. A. Sayfutdinova; O. A. Fakhrutdinova; A. A. Nafeevа (Детские инфекции (Москва))
Intrauterine infections are one of the most pressing health problems. A feature of listeria infection is the possibility of penetration of the pathogen  through the placental barrier with the development of severe systemic  lesions and negative perinatal outcomes.Purpose: To describe the nonspecific morphological manifestations of listeria infection in the early stages of the disease in postnatal fetal death.Morphological confirmation of listeriosis is multiple productive-necrotic granulomas (listeriomas) with the presence of listeria in them in the form of straight, short, sometimes ovoid rods, located singly or in groups, identified by Gram-Weigert staining.